2020
DOI: 10.1002/lio2.430
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction technique following total laryngectomy affects swallowing outcomes

Abstract: Objectives How reconstruction affects function following total laryngectomy is unclear. This study seeks to determine whether reconstruction method is associated with differences in swallowing outcomes. Methods Retrospective review of reconstruction technique in patients undergoing TL was compared by pharyngeal transit time (PTT), patient‐reported dysphagia (EAT‐10), and diet‐tolerated (FOIS). Results Ninety‐five patients met inclusion criteria, with 40 patients (42.1%) undergoing primary closure and 55 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
(46 reference statements)
1
27
1
Order By: Relevance
“…This reached significance in the MDADI functional subscale while approaching significance in all other subscales as well as the composite score. To the best of our knowledge, only one other study has compared dysphagiarelated outcomes by pharyngeal closure technique using a validated dysphagia index [10]. Harris et al used the EAT-10 questionnaire and in contrast to the present study, they found no significant difference in EAT-10 scores between PC, PMMF and FF pharyngeal closure [10].…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…This reached significance in the MDADI functional subscale while approaching significance in all other subscales as well as the composite score. To the best of our knowledge, only one other study has compared dysphagiarelated outcomes by pharyngeal closure technique using a validated dysphagia index [10]. Harris et al used the EAT-10 questionnaire and in contrast to the present study, they found no significant difference in EAT-10 scores between PC, PMMF and FF pharyngeal closure [10].…”
Section: Discussioncontrasting
confidence: 81%
“…To the best of our knowledge, only one other study has compared dysphagiarelated outcomes by pharyngeal closure technique using a validated dysphagia index [10]. Harris et al used the EAT-10 questionnaire and in contrast to the present study, they found no significant difference in EAT-10 scores between PC, PMMF and FF pharyngeal closure [10]. Other previous studies have compared patients by self-reported dysphagia or alternative measures of dysphagia such as diet consistency, feeding tube dependence or need for oesophageal dilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hui et al demonstrated that the narrowest width of the pharyngeal remnant (about 1.5 cm relaxed or 2.5 cm stretched) is sufficient both for primary closure and for restoration of swallowing function [53]. While these values are the theoretical lower limits of pharyngeal width that can be used in neopharyngeal reconstruction without significant stenosis, a larger neopharyngeal diameter does not correlate with better swallowing outcomes [53,54].…”
Section: Choosing Between Primary Closure or Other Reconstructionsmentioning
confidence: 99%
“…Total laryngectomy (TL) corresponds to the entire removal of the larynx 1 , and although this implies in a definitive dissociation between the digestive and respiratory tracts, postoperative anatomical impairments can affect oropharyngeal swallowing because the elevation of the larynx is eliminated and the propulsion of the tongue base is decreased, leading to a rupture of the constricting musculature of the pharynx, an increase in pharyngeal transit time, the presence of pharyngeal residues and a decrease in esophageal peristalsis [2][3][4][5] . Other pathophysiological aspects can also compromise swallowing after TL such as pseudodiverticulum, fistualization, stenosis, fibrosis, prosthesis leakage and gastroesophageal reflux 6 , in addition to sensory and motor impairment of the laryngeal nerves that innervate the pharynx 7 .…”
Section: Introductionmentioning
confidence: 99%